Genetic analysis of egg shell quality characters in layer chicken - KHATKAR, M S; SANDHU, J S; BRAH, G S; CHAUDHARY, M L (The Indian Journal of Animal Sciences, 2013)
Data were collected on 4538 pullets of 2 strains (PL 1 and PL 2) for various measures of shell-quality. Strain PL 2 had higher production body weight and better shell-quality. Sex linked genetie effects appearedto be important in most of the shell-quality characters. The pooled sire-component heritabilities (%) for PL 1 and PL 2, respectively, were: 39±9 and 49± 11 for shell thickness; 4S± 10 and 40± 1 0 for specific gravity;40±9 and 31±8 for% shell; and 43±10 and 27±8 for egg weight. Egg weight had positive genetic correlations with the other measures of shell quality. The genetic correlations all long the various measures of shell quality were all greater than 0.89 and as high as unity.